Mental Health Challenges in Women in Low- and Middle-Income Countries (LMICs): A Scoping Review - Aquartuti Tri Darmayanti; Joko Tri Atmojo; Aris Widiyanto; Hakim Anasulfalah; Ahmad Syauqi Mubarok; Atina Maya Fadhila (Journal of Language and Health, 2025)
Women are more likely than men to experience common mental disorders, especially in Low-Middle Income Countries (LMIC). Mental disorders contribute substantially to global disability. Overcoming this problem should be come to the priority. This review aims to synthesize the current understanding of the mental health challenges in women in low middle income country based on socioeconomic status, stigma, and integration with primary care. This scoping review was conducted following the framework outlined by Arksey and O'Malley. A literature search was conducted in the following databases: PubMed, Scopus, and Web of Science. Additionally, grey literature was searched through the World Health Organization and regional health ministries. Articles published since 2016-2026 were included.  Keywords and phrases related to "mental health OR Depression OR post-traumatic stress disorder OR Anxiety," AND "women OR Mothers" "low- and middle-income countries," "Poverty OR Food insecurity OR Unemployment OR Joblessness," "stigma OR Gender Inequity" and "primary care integration."  A qualitative synthesis of the extracted data was performed by thematic analysis. Poverty, unemployment, and unsafe social environments consistently emerge as major structural determinants that increase women’s vulnerability to depression, anxiety, and post-traumatic stress disorder. Stigma remains a pervasive and cross-cutting barrier operating at public, self, and structural levels. Integrated primary care models show promising potential to mitigate some of these challenges. The findings underscore that improving women’s mental health in LMICs requires multilevel strategies that simultaneously address socioeconomic inequities, stigma reduction, and health system strengthening.